Optimization of Cr(VI) removal by sulfate-reducing bacteria using response surface methodology. Issue 24 (20th May 2016) - Ahmadi, R.; Rezaee, A.; Anvari, M.; Hossini, H.; Rastegar, S.O.
Abstract: The aim of this work was to optimize Cr(VI) removal using sulfate-reducing bacteria from wastewater. Three effective factors including initial pH, initial Cr(VI) concentration, and inoculation percentage were optimized using a central composite design of response surface methodology. The optimum conditions were initial pH 7.5, initial Cr(VI) concentration 130 mg/l, and inoculation percentage 7.75%, and the maximum Cr(VI) removal was 82%. The kinetics study of Cr(VI) removal showed the pseudo-first-order model described experimental data better and was selected as an overall kinetic Cr(VI) removal.